2017
DOI: 10.1177/1010428317707881
|View full text |Cite
|
Sign up to set email alerts
|

MFG-E8 overexpression promotes colorectal cancer progression via AKT/MMPs signalling

Abstract: Several studies have revealed that MFG-E8 (milk fat globule-epidermal growth factor 8) is related to tumour development and progression. However, the relationship between MFG-E8 expression and metastasis in colorectal cancer patients and the role of MFG-E8 in colorectal cancer invasion and progression remain unknown. In this study, we performed immunohistochemistry and quantitative real-time polymerase chain reaction to assess MFG-E8 expression in colorectal cancer and adjacent non-cancerous tissues. Colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 37 publications
(70 reference statements)
3
43
0
Order By: Relevance
“…Our study also showed that the RFS and OS of the high MFG‐E8 expression group were significantly worse than those of the low‐expression group. These findings are consistent with the previous reports …”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our study also showed that the RFS and OS of the high MFG‐E8 expression group were significantly worse than those of the low‐expression group. These findings are consistent with the previous reports …”
Section: Discussionsupporting
confidence: 94%
“…We examined MFG‐E8 expression in human esophageal squamous cell carcinoma using IHC staining and found that some of the cells abundantly express MFG‐E8, as shown in other types of cancer . As the IHC staining of the samples showed that the expression of MFG‐E8 was more abundant in cancer cells than in macrophages or other stromal cells, MFG‐E8 from cancer cells appears to play an important role in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Invasion and migration have been acknowledged as the most lethal attributes of solid tumors and account for the majority of metastases [17]. Tumor cells have the ability to migrate from the original site to the blood and lymph, and invade surrounding or distant tissues, causing metastasis.…”
Section: Discussionmentioning
confidence: 99%